Meno: Virtue as οὐσία and εἶδος - Jankauskas, Skirmantas (Problemos, 2022)
The article is an interpretation of the first part of the Meno (70a-79e), in which Plato deals with the problem of knowledge of virtue. Parmenides’ being, constituted by Justice, becomes a reference point for reflecting on the ontological and cognitive profile of virtue. The polemic with the sophists forces Plato to reflect on the subject of philosophizing and to realize that it is existentially rooted in the ontologised language. Here Plato finds the concept of οὐσία, which becomes for him the cognitive prototype of virtue. For οὐσία as a possession presupposes the property of a thing whose meaning is determined not by the sensually ascertainable properties of a thing, but by its social significance, which is relatively constant and correlated with justice. The distinction between the meanings of a thing and of its possession in the same object conveys the idea that virtue as a human possession, i.e., οὐσία, cannot be known in everyday thinking that hypertrophies the senses, but should be present in an alternative layer of thinking, and thus imply an alternative mode of knowledge. It can therefore be surmised that Plato’s discovery of the duality of the concept of οὐσία inspired in him both the idea of an autonomous world of ideas and the idea of a specific way of accessing it, i.e. the theory of anamnesis.
Keywords: being; justice; virtue; οὐσία; property